Bloodshed and Meaning for the Life of the Sumbanese in the Pasola Tradition - Lambok Hermanto Sihombing; Maria Paskalia Aninda (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2022)
Indonesia has various performing arts. One of them is Pasola, a traditional war tradition from West Sumba, NTT region. This study aims to investigate the meaning and philosophical principles underlying the Pasola tradition. The research is classified as cultural research employing qualitative descriptive techniques. According to Edward Burnett Tylor (1832-19721), culture is a complex system consisting of learned human knowledge, belief, art, morals, law, conventions, abilities, and habits. To investigate the Pasola tradition, a descriptive qualitative strategy is employed by referencing multiple literature sources and observations from interviews broadcast on social media platforms such as YouTube. The objective of this paper is first to comprehend the philosophical significance of the Pasola tradition of the West Sumba tribe in greater depth. Second, raise everyone's awareness of the need to establish a pattern of subject-subject interactions or relationships to establish a healthy relationship between humans and nature. As a result, the government stakeholders are helped by society to implement sustainable development promoting cultural preservation.